The effects of isradipine on TGF-ß1 and type IV collagen expression in neonatal streptozotocin diabetic nephropathy - KAYA DAĞISTANLI, Fatma; TUNÇDEMİR, Matem and ÖZTÜRK, Melek (Cerrahpaşa Medical Journal, 2019)
The effects of isradipine on TGF-ß1 and type IV collagen expression in neonatal STZ diabetic nephropathy In this study, the effects of isradipine as a calcium channel blocker, on glomerulus structural alterations and renal functions were examined in the neonatal streptozotocin diabetes (n-STZ) model. We used 4 groups of newborn Wistar rats. On the 2nd day of birth after STZ (100 mg/kg) injection to the 1st and 2nd group, isradipine (5 mg/kg, i.p) was administered to the 2nd group for 6 weeks from 12 weeks on. The 3rd group was isradipine treated (5 mg/kg, i.p., from 6 weeks to 12 weeks) control group and the 4th group was healty control. During the period of the experiment, blood glucose levels, body weight and microalbuminuria level of the rats were measured. Kidneys were weighted. Tissue sections were immunostained using monoclonal type IV collagen and TGF-ß1 antibodies. The blood glucose levels were markedly decreased in the isradipine treated cortrols. Microalbuminuria levels were decreased in treated diabetics compared to diabetic group. Kidney weights were increased in n-STZ diabetics when compared to non-diabetics. Glomeruli dimensions of n-STZ diabetics were increased in comparison to nondiabetic control group. In the isradipine treated diabetic group the larger glomeruli were observed according to the nondiabetic group. Basal membrane thickening in glomerulus and significant increase in mesangial matrix and mesangial cells and an increased type IV collagen and TGF-ß1 expression in n-STZ diabetics were observed. In the isradipine treated groups type IV collagen and TGF-ß1 immunoreactivity in glomerulus were seen to be similar to nondiabetic controls. Our results show that isradipine could be effective in delaying the progression of nephropathy by decreasing microalbuminuria and blood glucose levels but it didnot completly improved renal morphology.